Expressive and Commissive Speech Acts in the 2024 Indonesian Presidential Debate: A Pragmatic Analysis on TvOne YouTube Channel - Henita; Inamul Azad (JPI: Jurnal Pustaka Indonesia, 2024)
Political debates serve as critical arenas for candidates to demonstrate credibility, convey policy agendas, and persuade audiences through carefully constructed discourse, with speech acts functioning as key pragmatic tools. This study aimed to analyze the use of expressive and commissive speech acts in the 2024 Indonesian presidential debate as broadcast on the YouTube channel TvOne News. Employing a qualitative descriptive design, the research collected utterances from the debate and analyzed them using pragmatic and speech act frameworks through stages of data reduction, classification, and interpretation, supported by triangulation for validity. The results revealed that expressive speech acts—including thanking, apologizing, criticizing, praising, and insinuating—were strategically employed to manage interpersonal relations and construct ethos, while commissive acts such as promising, offering, vowing, swearing, and expressing intention were used to project commitments and strengthen credibility. The discussion highlights that the candidates frequently combined expressive and commissive acts into composite strategies, thereby enhancing persuasive impact and appealing to both cultural expectations of politeness and digital media dynamics. The implication of this study is that the interplay between expressive and commissive acts in political debates not only enriches the theoretical understanding of political pragmatics but also offers practical insights for strengthening media literacy, enabling voters to critically interpret rhetorical strategies in the evolving digital campaign landscape.